A Versatile Clustered Regularly Interspaced Palindromic Repeats Toolbox to Study Neurological CaV3.2 Channelopathies by Promoter-Mediated Transcription Control - Tsortouktzidis, Despina; Tröscher, Anna R.; Schulz, Herbert; Opitz, Thoralf; Schoch, Susanne; Becker, Albert J.; van Loo, Karen M. J. (Frontiers in Molecular Neuroscience, 2022)
Precise genome editing in combination with viral delivery systems provides a valuable tool for neuroscience research. Traditionally, the role of genes in neuronal circuits has been addressed by overexpression or knock-out/knock-down systems. However, those techniques do not manipulate the endogenous loci and therefore have limitations. Those constraints include that many genes exhibit extensive alternative splicing, which can be regulated by neuronal activity. This complexity cannot be easily reproduced by overexpression of one protein variant. The CRISPR activation and interference/inhibition systems (CRISPRa/i) directed to promoter sequences can modulate the expression of selected target genes in a highly specific manner. This strategy could be particularly useful for the overexpression of large proteins and for alternatively spliced genes, e.g. for studying large ion channels known to be affected in ion channelopathies in a variety of neurological diseases. Here, we demonstrate the feasibility of a newly developed CRISPRa/i toolbox to manipulate the promoter activity of the Cacna1h gene. Impaired, function of the low-voltage-activated T-Type calcium channel CaV3.2 is involved in genetic/mutational as well as acquired/transcriptional channelopathies that emerge with epileptic seizures. We show CRISPR-induced activation and inhibition of the Cacna1h locus in NS20Y cells and primary cortical neurons, as well as activation in mouse organotypic slice cultures. In future applications, the system offers the intriguing perspective to study functional effects of gain-of-function or loss-of-function variations in the Cacna1h gene in more detail. A better understanding of CaV3.2 channelopathies might result in a major advancement in the pharmacotherapy of CaV3.2 channelopathy diseases.